Opportunities and challenges doing interdisciplinary research: what can we learn from studies of ethnicity, inequality and place?. Issue 17 (10th December 2019) - Finney, Nissa; Clark, Ken; Nazroo, James
ABSTRACT: This Special Issue Introduction critically reflects on the interdisciplinary working project on ethnicity, inequality and place undertaken by the ESRC Centre on Dynamics of Ethnicity. We argue that CoDE is uniquely placed to undertake this interdisciplinary work and discuss the extent to which the project pushed thinking beyond that of our disciplinary homes to provide innovative insights into the significance of place for understanding ethnic inequalities and identities. From the six papers in the Special Issue, this Introduction identifies four cross-cutting themes on ethnicity and place: processes of exclusion, the importance of temporal context and change, tensions of scale in the way ethnicity and place together shape experiences and inequalities, and the conceptualisation of ethnicity as dynamic, multi-faceted and socially constructed. We argue that the project has succeeded in terms of cross fertilisation of ideas, challenging ontological and epistemological divisions, and facilitating interdisciplinary learning, adaptation and appreciation. We also identify difficulties that were experienced. We suggest that interdisciplinary ideas flourish in an environment where they can fail and conflict, but where failure and conflict does not disrupt the underlying momentum of the work. We conclude in favour of interdisciplinary, democratic and co-produced research as a tool for social change.